Single source split filter dual energy: Image quality and liver lesion detection in abdominal CT - Eichler, Mathis; May, Matthias; Wiesmüller, Marco; Saake, Marc; Heiß, Rafael; Uder, Michael; Wüst, Wolfgang (European Journal of Radiology, 2020)
Purpose: Aim of this study was to evaluate image quality of single source dual energy CT (SSDE-CT) using split filter technique in oncologic abdominal CT. Method: 51 consecutive patients with newly diagnosed breast carcinoma were prospectively enrolled in this study and underwent a staging examination of the abdomen using SSDE-CT (120 kV, split filter technique, 400 ref. mAs). Inline default images (DI) and post-processed virtual monoenergetic images at 40 keV, 50 keV, 60 keV, 70 keV and 80 keV were reconstructed. Objective image quality was evaluated as contrast to noise ratio (CNR) for liver parenchyma, portal vein, spleen, pancreas, aorta and hypoattenuating liver lesions. Subjective image quality was rated on a 5-point scale. Image quality at different keV settings was analyzed in paired t-tests. Results: CNR was highest at 40 keV for vessels (portal vein: 9.0, aorta: 8.8, all p < 0.001) and for upper abdominal organs (spleen: 4.8, all p < 0.001; pancreas: 2.7, all p < 0.01 except p = 0.93 for 50 keV; liver parenchyma: 3.4, all p < 0.01). Highest CNR values for hypoattenuating liver lesions were found at 40 keV (7.7, all p < 0.001). Overall subjective image quality was highest with 80 keV and DI (both 4.8, all p < 0.001). Artifacts were most pronounced at 40 keV. Conclusions: High image quality can be obtained with SSDE-CT of the abdomen. Lowest monoenergetic reconstructions provide the highest image contrast and should be used for vessel evaluation. The best trade-off between artifacts and parenchymal contrast can be obtained with 80 keV images.
CRIS-Team Scopus Importer:2020-03-10
Keywords: Abdominal imaging; Breast carcinoma; Single source dual energy